Աղուանքում Արշակունեաց թագաւորութեան անկման ժամանակի մասին - Յակոբեան, Ալեքսան (Ասողիկ հրատ.)
The article summarizes the facts that allow to date the end of reign of Albanien king Vachagan II to 523 A. D. - the time of king Kavad's reform which resulted to а downfall of Iberian king Gurgen's reign. The issuing of two coins with monogram 'I'n (=ARAN) on 35-th year of Kavad's reign (522/523 A.D.) also supports the facts in the article.
Keywords: Հայոց պատմություն